Diversity and communities of culturable endophytic fungi from different tree peonies (geoherbs and non-geoherbs), and their biosynthetic potential analysis - Yang,Guodong (2018)
Abstract To know more about the potential roles of endophytic fungi in the formation mechanism of Daodi medicinal material, diversity and communities of culturable endophytic fungi in three types of tree peonies were investigated. Endophytic fungi of three types of tree peonies were isolated and identified. The diversity was analyzed. Bayesian trees constructed by MrBayes 3.2.6 after phylogenetic analysis of the ITS sequences. The endophytic fungi potential for synthesis of natural products was assessed by means of detecting NRPS and PKS gene sequences. In total, 364 endophytic fungi isolates representing 26 genera were recovered from Paeonia ostii ‘Feng Dan’, Paeonia ostii ‘Luoyang Feng Dan’, and Paeonia suffruticosa ‘Luoyang Hong’. More culturable endophytic fungi appeared in P. suffruticosa ‘Luoyang Hong’ (206) compared with P. ostii ‘Feng Dan’ (60) and P. ostii ‘Luoyang Feng Dan’ (98). The fungal community of P. ostii ‘Feng Dan’ had the highest richness and diversity. PKSs and NRPS detection rates of endophytic fungi from P. ostii ‘Feng Dan’ are both the highest among the three types of tree peonies. Results indicate that endophytic fungus is an important factor of Daodi Cortex Moutan forming, and endophytic fungi in peony are related to genuineness of Cortex Moutan.